PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE : Studi Empiris Pada Perusahaan Food and Beverage Yang Terdaftar Di Bursa Efek Indonesia 2019-2022 - Noorprasetya, Yogie; Prasetya, Mutiara Tresna (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This study aims to determine the effect of good corporate governance and corporate social responsibility on tax avoidance. good corporate governance is proxied by the independent commissioner and the audit committee, while corporate social responsibility is proxied by the corporate social responsibility disclosure index (CSRDI) and tax avoidance is proxied by the current ETR. corporate social responsibility disclosure index and measured based on the global reporting initiative 4.0. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022, namely 31 companies. The research sample consisted of 17 companies or 68 observational data selected by purposive sampling method. The data used is secondary data obtained from the website of the Indonesia Stock Exchange (IDX) and the data analysis used is multiple linear regression analysis. The results of the study prove that the independent commissioner and corporate social responsibility have a significant effect on tax avoidance, while the audit committee has no effect on tax avoidance. independent commissioners have an effect on tax avoidance because commissioners play an active role in supervising the actions of company management, while corporate social responsibility can be used as a deduction from the company's pre-tax profit so that it affects tax avoidance.